4.7k views
0 votes
-X + 9y = 363x + 3y = 42How would I answer this using the substitution method?

User Mattty
by
6.7k points

1 Answer

5 votes

Answer:

(9, 5)

Step-by-step explanation:

Given the simultaneous equation;

-X + 9y = 36 .... 1

3x + 3y = 42 ... 2

Multiply equation 1 through by -1 to have;

x - 9y = -36 ....1

3x + 3y = 42 ... 2

From 1;

x = -36 + 9y ....3

Substitute equation 3 into 2;

3(-36+9y) + 3y = 42

Open the parenthesis

-108 + 27y + 3y = 42

-108 + 30y = 42

30y = 42 + 108

30y = 150

y = 150/30

y = 5

Substitute y = 5 into equation 3;

From 3;

x = -36 + 9y

x = -36 + 9(5)

x = -36 + 45

x = 9

Hence the solution to the system of equation is (9, 5)

User Hardik Gajjar
by
6.1k points